2013
DOI: 10.5966/sctm.2012-0138
|View full text |Cite
|
Sign up to set email alerts
|

Developing High-Fidelity Hepatotoxicity Models From Pluripotent Stem Cells

Abstract: Faithfully recapitulating human physiology "in a dish" from a renewable source remains a holy grail for medicine and pharma. Many procedures have been described that, to a limited extent, exhibit human tissue-specific function in vitro. In particular, incomplete cellular differentiation and/or the loss of cell phenotype postdifferentiation play a major part in this void. We have developed an interdisciplinary approach to address this problem, using skill sets in cell biology, materials chemistry, and pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 8 publications
4
97
0
1
Order By: Relevance
“…Cell Culture and Differentiation hESCs (H9) and iPSCs (33D6) were cultured as described [16,[18][19][20] and maintained in a humidified 37°C, 5% CO 2 incubator. At day 9, differentiating cells from hESCs and iPSCs were cultured in hepatocyte maturation medium HepatoZYME (Life Technologies, Carlsbad, CA, http://www.lifetech.com) containing 1% Glutamax (Life Technologies), supplemented with 10 mM hydrocortisone 21-hemisuccinate (Sigma-Aldrich, St. Louis, MO, http://www.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Culture and Differentiation hESCs (H9) and iPSCs (33D6) were cultured as described [16,[18][19][20] and maintained in a humidified 37°C, 5% CO 2 incubator. At day 9, differentiating cells from hESCs and iPSCs were cultured in hepatocyte maturation medium HepatoZYME (Life Technologies, Carlsbad, CA, http://www.lifetech.com) containing 1% Glutamax (Life Technologies), supplemented with 10 mM hydrocortisone 21-hemisuccinate (Sigma-Aldrich, St. Louis, MO, http://www.…”
Section: Methodsmentioning
confidence: 99%
“…Human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) are examples of renewable cell populations [9,10]. Both populations have been shown to efficiently differentiate to hepatocytes by either spontaneous or directed differentiation and, therefore, offer significant promise in the quest to deliver a new wave of predictive human models [11][12][13][14][15][16][17][18][19]. In this vein, we have developed highly efficient, scalable, and serum-free differentiation procedures that are compatible with pluripotent stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human induced pluripotent stem cell (iPSC)-derived hepatocyte-like cells (HLCs) are expected to be useful for the prediction of DILI in the early phase of drug development. Many groups, including our own, have reported that the human iPS-HLCs have the ability to metabolize drugs, and thus these cells could be used to detect the cytotoxicity of drugs that are known to cause DILI (1,2). However, to accurately predict DILI, it will be necessary to establish a panel of human iPS-HLCs that better represents the genetic variation of the human population because there are large interindividual differences in the drug metabolism capacity and drug responsiveness of hepatocytes (3).…”
mentioning
confidence: 99%
“…However, it is discussed controversially to which degree stem cell-derived cells resemble primary cells. In the field of stem cell-derived hepatocyte-like cells, some authors reported that generation of 'functional,' 'high fidelity' hepatocytes from stem and precursor cells is already possible (Medine et al 2013;Szkolnicka et al 2014;Huang et al 2014), while others present a more critical point of view Hengstler et al 2005;Brulport et al 2007).…”
mentioning
confidence: 99%